2006
DOI: 10.1177/172460080602100406
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Role of Chromogranin A as a Prognostic Factor in Organ-Confined Prostate Cancer

Abstract: ABSTRACT:The clinical significance of neuroendocrine differentiation in patients who have undergone surgery for localized prostate cancer is still unclear. The aims of this study were to assess the relationship between serum neuroendocrine markers and well-known prognostic factors in prostate cancer (pathological staging, definitive Gleason score and serum PSA) and to search for correlations between serum chromogranin A (CgA) levels and pathological findings. Forty-one consecutive patients who had undergone ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Neuroendocrine differentiation also appeared to be associated with the androgen-refractory state and a poor prognosis [6,23-26]. It was reported that prostate cancer with a significant NE component is common in the advanced stage of the disease, especially in those patients who do not have elevated serum PSA levels [7,25,27,28], but its diagnostic role in non metastatic disease is still a matter of debate [8,29,30]. We analyzed serum CgA levels in patients who were diagnosed with a prostate cancer before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine differentiation also appeared to be associated with the androgen-refractory state and a poor prognosis [6,23-26]. It was reported that prostate cancer with a significant NE component is common in the advanced stage of the disease, especially in those patients who do not have elevated serum PSA levels [7,25,27,28], but its diagnostic role in non metastatic disease is still a matter of debate [8,29,30]. We analyzed serum CgA levels in patients who were diagnosed with a prostate cancer before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty‐three of these studies correlated the presence of neuroendocrine staining to patient outcomes such as biochemical recurrence, clinical progression, overall survival and prostate cancer‐specific survival. The characteristics of the included studies are summarized in Table 1 [19–80] and Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies also assessed the prognostic value of serum CgA expression in prostate patients, with controversial results [22][23][24][25]. Elevated serum CgA was reported to be an independent prognostic factor for OS and progression-free survival in CRPC patients treated with abiraterone acetate [26] and was related to advanced tumor stage and higher GS [27]. An elevated serum CgA level over three times the upper normal limit in mCRPC patients was a prognostic factor in patients treated with enzalutamide [28].…”
Section: Discussionmentioning
confidence: 99%